The effect of transition metal carbides MeC (Me = Ti, Zr, Nb, Ta, and W) on mechanical properties of B4C ceramics fabricated via pressureless sintering. Issue 17 (1st December 2020) - Liu, Guanqi; Chen, Shixing; Zhao, Yanwei; Fu, Yudong; Wang, Yujin
Abstract: In this study, boron carbide-metallic boride (B4 C-MeBx, Me = Ti, Zr, Nb, Ta, or W) multiphase ceramics were fabricated via in situ pressureless sintering at 2250 °C for 1 h. The effects of transition metal carbides, namely, TiC, ZrC, NbC, TaC, and WC, on the phase composition, microstructure, and mechanical properties of the ceramics were investigated. The results showed that MeC could facilitate the sintering densification of B4 C by distributing second-phase particles uniformly throughout the B4 C. Additionally, the main phases observed were B4 C and (Me, W)Bx (Me = Ti, Zr, Nb, or Ta) due to the doping of a small amount of WC during the ball milling process. As a result, the mechanical properties of B4 C-MeBx showed significant improvements when compared with those of single-phase B4 C ceramics. B4 C–NbB2 ceramics were found to exhibit the best mechanical properties, with an elastic modulus of 393.0 GPa, a hardness of 28.7 GPa, a flexural strength of 368.0 MPa, and a fracture toughness of 6.94 MPa m 1/2 .